World of UCL - Brewis, Georgina; North, John; Harte, Negley (Comparative Literature and Culture, 2018)
From its foundation in 1826, UCL embraced a progressive and pioneering spirit. It was the first university in England to admit students regardless of religion and made higher education affordable and accessible to a much broader section of society. It was also effectively the first university to welcome women on equal terms with men. From the outset UCL showed a commitment to innovative ideas and new methods of teaching and research. This book charts the history of UCL from 1826 through to the present day, highlighting its many contributions to society in Britain and around the world. It covers the expansion of the university through the growth in student numbers and institutional mergers. It documents shifts in governance throughout the years and the changing social and economic context in which UCL operated, including challenging periods of reconstruction after two World Wars.